2014
DOI: 10.1371/journal.pone.0092040
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Adolescent Boys' Physical Activity: Bout Length and the Influence of Accelerometer Epoch Length

Abstract: ObjectivesAccurate, objective measurement is important for understanding adolescents' physical activity (PA) behaviour. When using accelerometry to objectively measure PA, a decision must be made regarding how frequently data is recorded (i.e., epoch length). The purpose of this study was to examine i) PA bout length, and ii) the effect of variations in accelerometer epoch length on PA estimates during physical education (PE) and leisure time in adolescent boys.DesignCross-sectional study.MethodsYear 9 boys (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(90 citation statements)
references
References 34 publications
6
82
1
1
Order By: Relevance
“…For instance, heterogeneity in the application of cut-points to define PA intensities may have contributed to inconsistency in results, as described earlier in relation to LPA (Kwon et al 2011;Carson et al 2013). Similarly, the use of different sampling intervals ("epochs") has historically been dictated by accelerometer capability; however, the use of longer epochs (e.g., 60 s) in some studies is likely to have underestimated the volume of higher intensity PA, particularly in this population where the majority of MVPA occurs in bouts of ≤5 s in duration (Sanders et al 2014). Finally, objective measures of PA cannot accurately quantify some fitness activities (e.g., weight training), and until recently could not measure water-based activities; this may have resulted in an underestimation or overestimation of true effects in the present study.…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 94%
See 1 more Smart Citation
“…For instance, heterogeneity in the application of cut-points to define PA intensities may have contributed to inconsistency in results, as described earlier in relation to LPA (Kwon et al 2011;Carson et al 2013). Similarly, the use of different sampling intervals ("epochs") has historically been dictated by accelerometer capability; however, the use of longer epochs (e.g., 60 s) in some studies is likely to have underestimated the volume of higher intensity PA, particularly in this population where the majority of MVPA occurs in bouts of ≤5 s in duration (Sanders et al 2014). Finally, objective measures of PA cannot accurately quantify some fitness activities (e.g., weight training), and until recently could not measure water-based activities; this may have resulted in an underestimation or overestimation of true effects in the present study.…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 94%
“…Finally, objective measures of PA cannot accurately quantify some fitness activities (e.g., weight training), and until recently could not measure water-based activities; this may have resulted in an underestimation or overestimation of true effects in the present study. To begin to address these limitations, future work should adhere to standardized accelerometry cut-points (Trost et al 2011) or adopt new analytic techniques such as pattern recognition (Freedson et al 2012;Trost et al 2014), and use shorter sampling intervals (Sanders et al 2014).…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 99%
“…We measured MVPA using 1 s epochs to accurately capture the sporadic PA bouts that occur during PE 27. We used vertical axis data to classify activity intensity using an MVPA cut point of ≥38.27 counts per 1 s (derived from a cut point of ≥574 counts per 15 s28).…”
Section: Methodsmentioning
confidence: 99%
“…Morgan and Borg [18] found that during prolonged work intervals the rate of RPE change is a responsive indicator of fatigue. They found a linear relationship between perceptual factors and physiological (oxygen uptake and heart rate) or physical (work rate) parameters in their 6-20 scale [20].…”
Section: Rate Of Perceived Exertion (Rpe)mentioning
confidence: 99%
“…Wearable devices like accelerometers are becoming more and popular to objectively monitor and assess free-living physical activity in all type of individuals (i.e., children, adolescents, adults, elderly, athletes, students...), because they can help overcome many of the limitations of most of the other methods used such as questionnaires or pedometers [17]. Accelerometers can provide objective, time-stamped data of the intensity, frequency and duration of any complete program of physical activity performed without disturbing the individuals who wear those devices because of their small size [18]. To our knowledge, there are no published studies which have used accelerometers to assess the impact of amateur football practice in the players.…”
Section: Introductionmentioning
confidence: 99%